Pengembangan Manajemen Kegiatan Organisasi Kesiswaan Dan Ekstrakulikuler Pendidikan Agama Islam Dalam Pembinaan Budaya Keagamaan Di Smk Yapemi Pagelaran - Maesaroh, Siti; Salamun, Salamun (Jurnal Ilmiah Wahana Pendidikan, 2025)
This journal discusses the management of the PAI extracurricular program in fostering religious culture in students at SMK YAPEMI Pagelaran. This study aims to: 1) To determine the management of the PAI extracurricular program at SMK YAPEMI Pagelaran; 2) To determine the impact of the implementation of the PAI extracurricular program in fostering religious culture in students at SMK YAPEMI Pagelaran; and 3) To determine the supporting factors of the PAI extracurricular activity program in fostering religious culture in students at SMK YAPEMI Pagelaran. The type of research used is qualitative research with a descriptive approach. The subjects of the study were the Principal of SMK YAPEMI Pagelaran, Islamic Religious Education Subject Teachers at SMK YAPEMI Pagelaran, PAI Extracurricular Activity Instructors at SMK YAPEMI Pagelaran and students of SMK YAPEMI Pagelaran. The results of the study indicate that: 1) The management of the PAI extracurricular program at SMK YAPEMI Pagelaran includes: a) planning that begins with a coordination meeting to determine the objectives of the extracurricular program, selection of supervising teachers, activity time and facilities and infrastructure as well as funds for implementing activities, b) organizing which is carried out to show who is given full authority and responsibility to carry out PAI extracurricular activities, c) implementation, where the implementation of PAI extracurricular activities is carried out outside of school hours so as not to interfere with teaching and learning activities. Then in terms of material, it is in accordance with the existing syllabus and d) evaluation is carried out once every three months, where the results of the evaluation are then used as input for improving the implementation of PAI extracurricular activities in the following period; 2) The impact of the implementation of the PAI extracurricular program in fostering the religious culture of students at SMK Yapemi Pagelaran includes: the formation of students' awareness of worship, increasing student discipline and growing social sensitivity and keeping away bad influences and 3) Supporting factors for the PAI extracurricular activity program in fostering the religious culture of students at SMK YAPEMI Pagelaran include students' interest and enthusiasm, support from students' parents and the availability of facilities and infrastructure.